VP16 A NICE Way To Manage Managed Access: Case Study In Muscular Dystrophy. (2019) - Kent, Emma; Paling, Thomas
Abstract : Introduction: Managed access arrangements (MAAs) represent a way of enabling patient access to promising treatments while collecting real world data to inform future health technology evaluations (HTE) and commissioning decisions. In July 2016, the National Institute for Health and Care Excellence (NICE) recommended Ataluren for treating Duchenne Muscular Dystrophy within a MAA. NICE is uniquely placed to oversee the implementation and monitoring of this MAA in collaboration with multiple stakeholders to ensure the final outputs meet the needs of a future HTE. Methods: NICE assembled an Ataluren Managed Access Oversight Committee (MAOC) consisting of representatives from the manufacturer, patient organisations, commissioning body and treatment centres. This group were to meet every six months under the chairmanship of NICE with the primary function of reviewing the progress of data collection and identifying operational challenges in implementing the terms of the arrangement. Results: The Ataluren MAOC has convened four times since the MAA commenced and these discussions identified a number of important actions. Data completeness was a concern and prompted stakeholders to collaborate on implementing measures to circumvent this, to ensure data quality for future HTE. Lack of awareness and understanding of the MAA in the patient community was highlighted and resulted in the production of lay information. A review of the statistical analysis plan resulted in the need for an agreement amendment. To ensure an audit trail and appropriate critique, NICE produced an amendment process to define and justify amendments made during the agreement term. Conclusions: MAOC meetings play an important role in monitoring the progress of MAAs and have ensured that implementation issues are identified promptly and resolved with input from key stakeholders. This process allows NICE to coordinate the work of stakeholders to facilitate the success of the MAA, and will be adopted in future NICE MAAs in ultra-rare diseases.